Fault Tolerant Vibration-Attenuation Controller Design for Uncertain Linear Structural Systems with Input Time-Delay and Saturation - Falu Weng; Yuanchun Ding; Liming Liang; Guoliang Yang (Shock and Vibration)
The problem of fault tolerant vibration-attenuation controller design for uncertain linear structural systems with control input time-delay and saturation is investigated in this paper. The objective of designing controllers is to guarantee the asymptotic stability of closed-loop systems while attenuate disturbance from earthquake excitation. Firstly, based on matrix transformation, the structural system is described as state-space model, which contains actuator fault, input signal time-delay and saturation at the same time. Based on the obtained model, an LMIs-based condition for the system to be stabilizable is deduced. By solving these LMIs, the controller is established for the closed-loop system to be stable with a prescribed level of disturbance attenuation. The condition is also extended to the uncertain case. Finally, an example is included to demonstrate the effectiveness of the proposed theorems.